PENENTUAN HARGA JUAL ATAS PESANAN KHUSUS PADA CV. CETAK JAYA MAKMUR (PENERAPAN VARIABEL COSTING) - Indriani, Devi (EKONOMIA, 2013)
There is two approach of which can taken management side in the plan and decision making that is by basing cost of good sold method of full and costing of variable costing. The condition which must be paid attention and become consideration that is : improving profit, capacities still available enough order, special order do not bother or destroy product marketing of company.